Catalog of Judeo-Persian Manuscripts in the Library of the Jewish Theological Seminary of America. - Moreen, Vera Basch (Études sur le judaïsme médiéval., 2014)
The Judeo-Persian manuscripts that Iranian Jews produced between the fifteenth and nineteenth centuries provide a thorough description of their intellectual parameters. They demonstrates the Jews' deep attachment to Judaism as well as their profound acculturation in Iran.